Contralateral Lower Limb Radiculopathy Following Minimally Invasive Oblique Lumbar Interbody Fusion in Treatment of Degenerative Lumbar Spine Disease - Nisarg Pravinchandra Parikh; Amit Chandrakant Jhala (Journal of Minimally Invasive Spine Surgery and Technique, 2021)
Objective To understand the etiology and solution for postoperative contralateral radiculopathy following Minimally Invasive oblique Lumbar Interbody Fusion (MIS OLIF) performed in degenerative lumbar spine disorders. There is lack of sufficient data on contralateral radiculopathy occurring after MIS OLIF. OLIF is an increasingly used procedure performed for degenerative lumbar spine disorders. So, it is important to understand the etiology and solution of potentially avoidable complication. Methods Retrospective analysis of 74 consecutive patients with total 97 segments operated was done from May 2016 to December 2019 in whom minimal access oblique lumbar interbody fusion was carried out. All the perioperative complications were noted and patients with contralateral radiculopathy were analyzed clinically and radiologically and etiology for this complication. All these patients followed up at 1, 3, 6 and 12 months postoperatively. Results Contralateral radiculopathy was noted in 6 patients (8.1%). Four patients had only pain in opposite limb, 1 patient had partial sensory loss and 1 patient had partial motor loss in addition to pain. Direct decompression was performed in 3 patients whereas 3 patients were managed conservatively. All the patients had complete resolution of pain at 3 months follow-up and there was partial motor and sensory recovery in affected patients. Conclusion Contralateral radiculopathy is a potential complication of MIS OLIF. It can be avoided with proper execution of surgical steps especially during cage preparation and proper patient selection is an important key too. Management can be surgical or non-surgical depending upon the etiology of this complication (design of study: retrospective study).